Analisis Kebutuhan Pengembangan Media Poster pada Mata Pelajaran IPAS Sekolah Dasar - Ulfatul Khasanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the needs for developing poster media in the Science and Social Studies (IPAS) subject at the elementary school level, specifically for fourth-grade students at SDIT Mutiara Insan, Sorong Regency. The research uses a descriptive quantitative approach with a survey method. The subjects consisted of 21 fourth-grade students who filled out a questionnaire with five dimensions: current use of learning media, need for AI-based posters, pedagogical aspects (learning experience), technical aspects (technology readiness), and motivation and interest aspects. Data analysis used descriptive statistics with percentage calculations. The results showed that the need for poster media development in IPAS subjects was in the high category across all dimensions, with an overall average of 78.2%. The technical readiness dimension obtained the highest score (80.4%), followed by the need for AI-based posters (78.7%), while pedagogical aspects, motivation, and current media use each obtained 77.3%, 77.3%, and 77.1% respectively. These findings indicate that fourth-grade students strongly feel the need for innovative and visually engaging AI-assisted poster media in their IPAS learning. Implications for designing effective, child-friendly, and curriculum-aligned poster media for elementary students are discussed.